The role of physiotherapy in sports medicine : perceptions of orthopaedic surgeons, sports physicians, biokinetics and physiotherapists - Sole, Gisela (Division of Physiotherapy, 2026)
A survey was undertaken to assess the perception of orthopaedic surgeons, sports physicians, biokineticists and physiotherapists of the role of physiotherapists in sports medicine. Orthopaedic surgeons (n=24), sports physicians (n=171 ), biokineticists (n=39) and physiotherapists (n=226) who were members of the South African Sports Medicine Association in 1995 were included in the study population. The questionnaire consisted of 36 tasks, which were divided into eight sections. Respondents were asked to rate the importance of the tasks for physiotherapists and the competence at which these tasks were performed by physiotherapists on a six-point Likert scale. Means, medians and standard deviations were calculated for the importance and the competence of each task as perceived by each professional group. The response rate was 54. 7% (n=252). All tasks were perceived to be "important" by physiotherapists (n=146) (median>3). The section on "injury prevention and epidemiology" generally received lower ratings of competence by the physiotherapists than the other sections. The orthopaedic surgeons (n=12), sports physicians (n=68) and biokineticists (n=22) generally perceived the importance of the tasks and the competence at which they were performed by physiotherapists lower than the physiotherapists (p<0.05 with the Kruskall-Wallis test). The differences in perception were greatest in tasks which overlapped with the scope of practice of the specific professional groups (p<0.017 with the Mann Whitney-U test). Kendall tau correlations and canonical correlations between importance of the tasks for physiotherapists and competence at which these were performed· by physiotherapists were low. The areas of "emergency care", "rehabilitation", "injury prevention" and "research" need to receive more attention in the training of sports physiotherapists.